Impact of mental disorders on health-related quality of life: a propensity score matched comparison - Koh, Seong-Jo; Lee, Yongpyo; Kwon, Hye-Young (Frontiers in Psychiatry, 2025)
BackgroundDespite the importance of the health-related quality of life (HRQoL) in mental health, research into HRQoL among people with mental disorders remains limited in Korea.AimsTo quantify the impact of mental disorders on HRQoL in the Korean context.MethodsPropensity score matching was used to establish a case-control database. A total of 177 people with mental disorders (38.4% with schizophrenia, 21.5% with bipolar affective disorder, 20.3% with recurrent depressive disorder and 19.8% with other mental conditions) were surveyed and matched with an equal number of individuals without mental disorders from the Korean National Health and Nutrition Examination Survey. HRQoL was measured using the EuroQol-5 Dimension (EQ-5D) scale. Multivariate beta regression analysis was performed to assess the impact of mental disorders on HRQoL.ResultsIndividuals with mental disorders had significantly lower EQ-5D index scores (0.854, SD 0.144) than those without mental disorders (0.972, SD 0.067) (p<0.0001). According to the results of the multivariate beta regression analysis, having a mental disorder was found to significantly worsen HRQoL by 71.2%(exp(-1.244)=0.288, p<0.0001). Additionally, self-rated health was found to significantly improve HRQoL in people with mental disorders. Rating one’s health as ‘good’ was associated with a 95.1% (β=0.668, p=0.0029) increase in EQ-5D score compared to rating it as ‘poor’.ConclusionThe presence of mental disorders was significantly associated with lower HRQoL. Further in-depth studies are needed to explore HRQoL among individuals with mental disorders from a variety of perspectives, particularly within the Korean context.